2021
DOI: 10.5551/jat.62448
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Distribution and Stability of Curved Basilar Artery Plaque: A Study Based on HR-MRI

Abstract: This study aims to evaluate the differences in the characteristics of atherosclerotic plaques in the proximal, curved, and distal segments of the curved basilar artery (BA) through high-resolution magnetic resonance imaging(HR-MRI). Methods:The imaging and clinical data of 146 patients were retrospectively analyzed. On the basis of threedimensional (3D) time -of -flight magnetic resonance angiography (3D-TOF-MRA), 51 patients with BA curvature were selected for the study. The BA plaque is divided into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The responsible blood vessels were determined based on the patient’s clinical symptoms and the location of the DWI diffusion limitation. The location of the responsible plaque was defined as the plaque at the same layer as the lesion or at the adjacent upper/lower layer ( 18 ), or the plaque at the narrowest point of the blood vessel. The presence or absence of intraplaque hemorrhage (IPH) and plaque enhancement were analyzed, and the signal intensity (SI) of the plaque and brain gray matter before and after enhancement was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The responsible blood vessels were determined based on the patient’s clinical symptoms and the location of the DWI diffusion limitation. The location of the responsible plaque was defined as the plaque at the same layer as the lesion or at the adjacent upper/lower layer ( 18 ), or the plaque at the narrowest point of the blood vessel. The presence or absence of intraplaque hemorrhage (IPH) and plaque enhancement were analyzed, and the signal intensity (SI) of the plaque and brain gray matter before and after enhancement was measured.…”
Section: Methodsmentioning
confidence: 99%
“…However, some researchers have found that IPH was also observed in asymptomatic carotid atherosclerotic plaques and plaques without stenosis 36,37) . In addition, a study suggested that plaques proximal to the BA are more prone to IPH 38) . A small number of plaques showed IPH in our study, and no difference was found between the two groups .…”
Section: Comparison Of Ba Plaque Characteristics and Mid-ba Angle Bet...mentioning
confidence: 99%
“…Most previous studies mainly focused on the relationship between the tortuosity of the BA and the plaque presence, location, and mean wall thickness 14,16,18,38) , or they only focused on differentiating plaque characteristics on HRMRI between symptomatic and asymptomatic patients 39) . However, very few studies have established the relationship between different mid-BA angle and plaque characteristics and pontine infarction when the BA has plaques.…”
Section: Comparison Of Ba Plaque Characteristics and Mid-ba Angle Bet...mentioning
confidence: 99%
“…With an improved quality of life and an aging population, ICAS-induced cerebrovascular diseases are increasingly prevalent in clinical practice [8] . Atherosclerotic plaque is the most important cause of stroke and is often associated with unstable plaques [9]. Intracranial atherosclerotic disease (ICAD) is defined as atherosclerotic lesions affecting the large intracranial artery at the bottom of the brain, including the intracranial carotid artery (ICA), middle cerebral artery (MCA) and basilar artery.…”
Section: Atherosclerosismentioning
confidence: 99%